Emerging Oral Nicotine Products and Periodontal Diseases - Dongxia Ye; Irfan Rahman (International Journal of Dentistry)
Oral nicotine pouches are emerging as a new “modern oral” nicotine product. These prefilled pouches contain nicotine, flavorings, and filling agents that dissolve in the mouth. Nicotine can be derived from tobacco leaf or chemical synthesis. Traces of TSNAs and toxic chromium were detected in the pouch products. This raises the concern about general and periodontal health. This review aims to update the current oral nicotine products research relating to periodontal disease and its relevance in periodontal inflammation. Nicotine interacts with host cells and affects inflammatory responses to microbial challenges. It may directly or indirectly deteriorate periodontal tissues by activating nicotinic acetylcholine receptors, repressing PDL fibroblasts cells, increasing cellular ROS and cytokines/chemokines, growth factors, breaking microbiota balance, and dysregulating miRNAs expression. Studies show that appealing flavorings contained in nicotine pouches pose harm to periodontal innate immune responses and increase penetration of nitrosamines. In addition, flavored ONPs increase the risk of dual or poly-tobacco products among young adults, stacking up detrimental effects on the periodontium. Given the recent growth of users, further studies are needed to elucidate the impact of ONPs, even poly-tobacco use, on systemic and periodontal health. Moreover, policymakers should ensure to avoid generating a new wave of nicotine addiction among youths in the U.S.